Rāgs of Western India and Sindh - Peter Manuel; Brian Bond (Analytical Approaches to World Music)
It is generally taken for granted that the rāg repertoire of Hindustani music is a pan-regional corpus, and that whatever regional origins and associations some rāgs may have once had are long since lost and inoperant. Accompanying this axiom is an assumption that rāgs are entities essentially unique to classical Hindustani and Karnatak musics. These notions, in fact, are only partially true, being marred by a significant exception, in the form of rāgs which are exclusive to or closely associated with Western India, by which we refer here to pre-Partition Punjab, Rajasthan, and Sindh. Some of these rāgs are part of the classical repertoire, but are only or predominantly performed by gharānās presently or historically based in the West. Others are part of the repertoire of Sikh gūrbānī sangı̄t, or are constituents of Rajasthani Langā and Mānganiyār music and Sindhi kāfī and shāh jo rāg̈. In this essay we survey these alternate rāg traditions and make a set of broader observations about their implications for North Indian music culture, including the nature and extent of regionalism therein, and the importance and, indeed, richness of these vernacular genres in the subcontinent’s music cultures.